Seismic Behavior of a Six-Span Simply Supported Bridge with Multiple Unseating Prevention Devices - Desi Setyowulan (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2010)
In earthquake-prone areas, a bridge is unavoidably attacked by an earthquake which has been noticed as the most frightened and destructive phenomenon of nature. Observed from the damaged bridges, column failure and deck unseating caused a more serious loss. The purpose of this study is to clarify the effectiveness of multiple unseating prevention devices for bridge by numerical simulations. The Vector Form Intrinsic Finite Element (VFIFE) is selected to be the analysis method, because it is superior in managing the engineering problems with material nonlinearity, discontinuity, large deformation, large displacement and arbitrary rigid body motions of deformable bodies. A six-span simply-supported bridge with rigid bearings and multiple unseating prevention devices (restrainer and stopper) is analyzed under near-field ground motions recorded at JR Takatory and JMA Kobe during the 1995 Japan Kobe earthquake. From the numerical analysis, it is found that installation of multiple unseating prevention devices is not effective to reduce unseating of the simple-supported bridge.